Boom and bust in Bronze Age Britain : the Great Orme copper mine and European trade - Williams, R. Alan, (Archaeopress Archaeology, 2023)
The Great Orme copper mine in North Wales is one of the largest surviving Bronze Age mines in Europe. This book presents new interdisciplinary research to reveal a copper mine of European importance, dominating Britain's copper supply from c. 1600-1400 BC, with some metal reaching mainland Europe - from Brittany to as far as the Baltic.